The Effectiveness of Online Learning in Elementary School Children: Efektifitas Pembelajaran Daring Pada Anak Sekolah Dasar - Lailatul Marfu'ah; Istikomah Istikomah (Academia Open, 2021)
In the times of Pandemic Covid-19, E-learning has become an activities learning model that should be done by all educational institutions in Indonesia, no exception at MI Nurul Huda Ngampelsari Candi Sidoarjo, Which a an activities learning model where an interaction between teacher and student through internet media. The e-learning Implementation requires the readiness of a learning management system, a teacher and student ability to use other applications based internet (digital talent), and student learning independence. Therefore, the aim research are; first, to descriptive a Implementation e-learning policy at MI Nurul Huda, and; Second, analysis effectivity e-learning to students at MI Nurul Huda. This Research uses descriptive qualitative approach with Miles - Hubermen Techniques Analysis, and Gibson Effectiveness Analysis Approach. Result this research are; First, The provisions for e-learning at MI Nurul Huda is outlined in Head Madrasah Decision Letter Number: KB/94.B-205/VII/2020 where the implementation to the teacher council by utilizing applications available on social media and utilizing packages by the Ministry of Education and Culture on TVRI. Second, Gibson Effectiveness Analysis show that e-learning system at MI Nurul Huda is not Effective. This is obtained from the low achievement of aim learning around 40%, and the low fulfillment in an effective learning system, around 36,6%. The percentage achievements are measured by the fulfillment of several components in the standardization of effective learning by theachers.